2021
DOI: 10.1001/jamanetworkopen.2021.17035
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Symptoms of Depression and Anxiety Among Women Experiencing Homelessness and Unstable Housing During the COVID-19 Pandemic

Abstract: had full access to all of the data in the study and take responsibility for the integrity of the data and the accuracy of the data analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…Unmet need for showers [ 12 , 39 ], bathrooms [ 97 ], and other hygiene products or services [ 44 , 97 ] for PEH during the pandemic were reported by several studies. In a study by Riley et al, [ 111 ] 66% of women experiencing homelessness or unstable housing reported one or more subsistence needs, defined as insufficient access to food, clothing, housing, or hygiene resources. In some cases, barriers to hygiene were exacerbated by the pandemic; reduced access to showers [ 88 , 94 , 109 ], toilets [ 94 ], laundry [ 88 , 94 ], and other personal hygiene products and services [ 13 ] were discussed by several studies, with some noting that barriers were due, at least in part, to public closures [ 12 , 94 , 97 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Unmet need for showers [ 12 , 39 ], bathrooms [ 97 ], and other hygiene products or services [ 44 , 97 ] for PEH during the pandemic were reported by several studies. In a study by Riley et al, [ 111 ] 66% of women experiencing homelessness or unstable housing reported one or more subsistence needs, defined as insufficient access to food, clothing, housing, or hygiene resources. In some cases, barriers to hygiene were exacerbated by the pandemic; reduced access to showers [ 88 , 94 , 109 ], toilets [ 94 ], laundry [ 88 , 94 ], and other personal hygiene products and services [ 13 ] were discussed by several studies, with some noting that barriers were due, at least in part, to public closures [ 12 , 94 , 97 , 109 ].…”
Section: Resultsmentioning
confidence: 99%
“…There were mixed impacts of the COVID-19 pandemic on access to food for PEH. Three studies reported unmet need for food during the pandemic [ 85 , 97 , 111 ]. Riley et al [ 111 ] measured subsistence needs, defined as insufficient access to food, clothing, housing, or hygiene resources, and found that 66% of women experiencing homelessness in the study had at least one unmet subsistence need.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations